مشكلة الإسكان ومؤشـرات الأزمة الحضرية في المجتمعات النامية - حسيبة, مـلاس (Sciences humaines, 2014)
تعد مشكلة الإسكان الحضري من المسائل الهامة التي عنيت بالبحث والدراسة من طرف المهتمين بقضايا المجتمع والتحضر منذ العقود الأولى من الألفية السابقة. إلا أنها أخذت حاليا اتجاها جديدا ينذر بكارثة حقيقية لاسيما في المجتمعات الفقيرة، وإزاء هذا الوضع حاولت العديد من الحكومات سن سياسات من شأنها استيعاب الأزمة والحد من النمو العشوائي للمدن، والذي غير من مورفولوجيتها الحضرية وشوه نسيجها العمراني، إلا أنها غالبا ما أثبتت عدم نجاعتها في توفير مستوى إسكان مناسب، في ظل قصور التشريعات وغياب التنمية الحضرية المحكمة والكفيلة بتحقيق التوازن بين الموارد الاقتصادية من جهة وبين حاجات المجتمع في مجال الإسكان من جهة أخرى.     Abstract:   The problem of urban housing is one of the  most important issues that concerned with  the study and attention by researchers and scholars in the social sciences since  the early decades of the previous millennium.But it became a global problem afflicting the poor countries , and about this situation , governments have attempted to develop urban programs that will accomodate the crisis and reduce unplanned growth of cities, which changed its urban morphology and distorted the fabric of adequate housing and suitable for human needs especially in the developing countries. And may be due primarily to inadequate legistation and lock of ability to find radical solutions and effective to the crisis in the steady increase of urban population on one hand , and lack of balance in economic development and urban on the other hand.